The conversion of subtropical forest to tea plantation changes the fungal community and the contribution of fungi to N2O production - Zheng, Ningguo; Yu, Yongxiang; Wang, Juan; Chapman, Stephen J.; Yao, Huaiying; Zhang, Yingying (Environmental pollution (1987), 2020)
The conversion of natural forests to tea plantations largely affects soil nitrous oxide (N2O) emissions and soil microbial communities. However, the impacts of this conversion on the contribution of fungi to N2O emission and on fungal community structure remain unclear. In this study, we determined the soil N2O emission rate, N2O production by fungi, associated fungal community diversity, and related ecological factors in chronological changes of tea crop systems (3, 36 and 105 years old tea orchards named T3, T36 and T105, respectively), and in an adjacent soil from a natural forest. The results indicate that the tea plantations significantly enhanced soil N2O production compared with the forest soil. Tea plantations significantly decreased soil pH and C/N ratio, but increased soil inorganic nitrogen (N). Furthermore, they increased the fungal contribution to the production of soil N2O, but decreased the bacterial counterpart. We also observed that fungal community and functional composition differed distinctly between tea plantations and forest. Additionally, most of the fungal groups in high N2O emission soils (T36 and T105) were identified as the genus Fusarium, which were positively correlated with soil N2O emissions. The variation in N2O emission response could be well explained by NO3−-N, soil organic carbon (SOC), C/N, and Fusarium, which contributed to up to 97% of the observed variance. Altogether, these findings provide significant direct evidence that the increase of soil N2O emissions and fungal communities be attributed to the conversion of natural forest to tea plantations. [Display omitted] •Forest-to-tea plantation conversion altered sources of N2O production.•Tea plantations have increased N2O production source from fungi.•Fungal communities differed following the conversion from forest to tea plantation.•Soil properties and Fusarium groups contributed to N2O emissions.